{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

1007slides_Part3

1007slides_Part3 - Math 1007 Fall 2006(These slides replace...

Info iconThis preview shows pages 1–7. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 1007, Fall 2006 (These slides replace neither the text book nor the lectures.) Part III: Differentiation 16. Differentiation: Four Basic Rules (33-37) 17. Product Rule and Quotient Rule (38-40) 18. The Derivative (41-44) 19. The Chain Rule (45-50) 20. Derivatives of Trigonometric Functions (51-54) 21. Derivatives of Exponential Functions (55-56) 22. Derivatives of Logarithmic Functions (57) 23. Implicit Differentiation (58-63) 24. Derivatives of Inverse Trig Functions (64-65) 25. Higher Order Derivatives (66-70) 26. Logarithmic Differentiation (71-74) 32 16. Differentiation: Four Basic Rules Rule 1: Derivative of a Constant d dx ( c ) = 0 ( c a constant) Rule 2: The Power Rule If n is any real number, then d dx ( x n ) = nx n- 1 Example 1 f ( x ) = x f ( x ) = d dx ( x ) = 1 x 1- 1 = x = 1 Example 2 f ( x ) = x 3 / 2 f ( x ) = d dx ( x 3 / 2 ) = 3 2 x 1 / 2 33 Rule 3: Derivative of a Constant Multiple of a Function d dx [ cf ( x )] = c d dx f ( x ) ( c a constant) Example 3 f ( x ) = 2 x 3 f ( x ) = d dx (2 x 3 ) = 2 d dx x 3 = 2 · (3 x 2 ) = 6 x 2 Rule 4: The Sum Rule d dx [ f ( x ) ± g ( x )] = d dx [ f ( x )] ± d dx [ g ( x )] Example 4 f ( x ) = 4 x 5 + 10 x 2 f ( x ) = d dx (4 x 5 ) + d dx 10 x 2 = 20 x 4 + 20 x 34 Problem: Find the slope and an equation of the tangent line to the graph of f ( x ) = 2 x + 1 √ x at the point (1 , 3). Solution f ( x ) = 2 x + 1 √ x = 2 x + x- 1 / 2 f ( x ) = 2- 1 2 x- 3 / 2 = 2- 1 2 x 3 / 2 f (1) = 2- 1 2(1) 3 / 2 = 2- 1 2 = 3 2 Using slope m = 3 2 and point ( x, y ) = (1 , 3) y = mx + b 3 = 3 2 (1) + b b = 3- 3 2 = 3 2 = ⇒ y = 3 2 x + 3 2 Hence the slope of the tangent is 3 / 2 and the equation of the tangent line is y = 3 2 x + 3 2 . 35 Application: Altitude of a Rocket The altitude of a rocket (in feet) t seconds into flight is s = f ( t ) =- t 3 + 96 t 2 + 195 t + 5 ( t ≥ 0) . Find the initial velocity of the rocket. Solution: Velocity is the derivative of Altitude The rocket’s velocity at any time t is v = f ( t ) =- 3 t 2 + 192 t + 195 Since f (0) = 195, the rocket’s initial velocity is 195 ft/second. 36 Application: Population Growth A study of Sunbelt projects that the town’s population in the next 3 years will grow according to P ( t ) = 50 , 000 + 30 t 3 / 2 + 20 t, where P ( t ) denotes the population t months from now. (a) How fast will the town’s population be increasing in 9 months? (b) in 16 months? Solution: The change in population is the derivative of population P ( t ) = 3 2 30 t 1 / 2 + 20 = 45 t 1 / 2 + 20 (a) In 9 months, the population change is P (9) = 45(9) 1 / 2 = 45 · 3 + 20 = 155 As this value is positive , the population is increasing by 155 people/month. (b) In 16 months, the population change is P (9) = 45(16) 1 / 2 = 45 · 4 + 20 = 200 , so the population is increasing by 200 people/month....
View Full Document

{[ snackBarMessage ]}

Page1 / 43

1007slides_Part3 - Math 1007 Fall 2006(These slides replace...

This preview shows document pages 1 - 7. Sign up to view the full document.

View Full Document Right Arrow Icon bookmark
Ask a homework question - tutors are online